An innovative six sigma and lean manufacturing approach for environmental friendly shipyard - Bilgili, L.; Deli, D.; Celebi, U. B. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2013)
Ship building is a very old and complex production method. It has many kinds of inputs and processes that are interconnected and each process has an effect on the next stages of a ship's life cycle. Thus, a good planning ought to be developed to make an efficient producing process. Besides, due to the growing environmental awareness, new and innovative methods must be used for manufacturing ships. Organizations have to interest in the issues that lowers the costs for efficiency and surviving in competitive environment. The companies make investments in shipbuilding industry are taking actions for minimization the costs. In this paper, six sigma and lean manufacturing approach are investigated to reach a more environmental friendly shipyard.
Keywords: PERFORMANCE; MANAGEMENT; Engineering; Environmental Sciences & Ecology; Materials Science